Is camel milk protein suitable for infants? Understanding mothers’ knowledge, attitudes, and practices - Morgambal Padayachee; Samir K. H. Safi; Monia Kittana; Hessa Salem Al Derei; Muneera Khajjah; Mozah Salem Obaid Khameis Aldhanhani; Hessa Mohammed Helal Alrashedi; Priti Mudgil; Sajid Maqsood; Amita Attlee (Frontiers in Sustainable Food Systems, 2025)
IntroductionCamel milk, with its resemblance to human milk and therapeutic properties, has potential as a substitute/complementary food for infants. To commercialize camel milk and its products specifically for infants, this research was imperative to explore the knowledge, attitudes, and practices among mothers about the acceptance of camel milk and its products for babies (0–2 years old) in the United Arab Emirates (UAE).MethodsUsing convenience sampling, a bilingual structured questionnaire with Cronbach-alpha-tested reliability of 0.865 was completed by 502 mothers, both UAE Nationals and expatriates.ResultsResults showed an inadequate awareness about exclusive breastfeeding, with only 54.7% aware of its correct duration. However, most participants (59.8%) did not know if it was suitable for use in babies, and 76.1% were not aware of any health benefits associated with its use in babies. Based on a five-point Likert scale (from 0–4), mean score exceeding neutral score of 2 indicated mothers’ positive attitudes toward camel milk and its products: culturally acceptable (2.77) and acceptable to their babies (3.09). Moreover, the current practice of using camel milk as an alternative to human milk was not reported in those mothers who did not breastfeed their babies. Furthermore, mothers’ employment, lower birth order of the babies, mothers’ knowledge about camel milk use for babies, its use in complementary foods, and associated health benefits emerged as factors significantly influencing their decision to use camel milk, its infant formula, and products in complementary feeds for the 0–2 years old babies.DiscussionOverall, promoting camel milk and its products as a sustainable nutritional alternative for 0–2 years old babies necessitates a multifaceted approach that includes raising awareness and fostering a positive attitude among mothers to support its acceptance. Future research should systematically explore consumer demand, maternal perceptions, and safety considerations, with a focus on establishing evidence-based guidelines for the appropriate use of camel milk products in early childhood nutrition.